1994
DOI: 10.1177/0022343394031003005
|View full text |Cite
|
Sign up to set email alerts
|

Peace among Democratic and Oligarchic Republics

Abstract: A list was compiled of virtually all significant military confrontations between republics throughout history. By including regimes only marginally republican, some forty cases were found from ancient Greece to the 1990s; about half of these had significant combat. Detailed historical investigation of each case reveals consistent patterns. A striking lack of wars between well-established democracies prevailed not only among modern states but also among earlier regimes commonly described as democracies, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The elimination of structural hierarchies, which are supported by norms of violence and oppression, should, therefore, result in less violence both domestically and internationally as norms of equality and non-violence are transferred to the international arena (Weart, 1994). Although the state has the power to minimize domestic inequalities, and thus to undermine structural inequalities, some states instead exacerbate these inequalities and power hierarchies through formal policies of state repression.…”
Section: Structural Violencementioning
confidence: 99%
“…The elimination of structural hierarchies, which are supported by norms of violence and oppression, should, therefore, result in less violence both domestically and internationally as norms of equality and non-violence are transferred to the international arena (Weart, 1994). Although the state has the power to minimize domestic inequalities, and thus to undermine structural inequalities, some states instead exacerbate these inequalities and power hierarchies through formal policies of state repression.…”
Section: Structural Violencementioning
confidence: 99%
“…The finding that democracies, while apparently engaging in war no less frequently than other states, seldom if ever fight one another is generally considered robust (Levy, 1989:270; Bremer, 1992; Ray, 1993, 1998; Weart, 1994:299, 1998; Russett and Oneal, 2001). When it comes to explaining it, however, there is considerable disagreement (Hagan, 1994:185–86).…”
Section: Explaining Democratic Peacementioning
confidence: 99%
“…With a few exceptions (Maoz and Abdolali, 1989;Weart, 1994;Leeds and Davis, 1995), most scholars have found that only democratic states share a special relationship, leading them to focus on characteristics unique to democracies like democratic norms or institutional constraints. However, if autocracies also favor 19 In the twentieth century, differences on the scope variable ranged from zero, suggesting very similar economic structures, to eight, suggesting large differences in economic institutions.…”
Section: Implications and Conclusionmentioning
confidence: 99%